2022
DOI: 10.7717/peerj.13267
|View full text |Cite
|
Sign up to set email alerts
|

A DNA barcode survey of insect biodiversity in Pakistan

Abstract: Although Pakistan has rich biodiversity, many groups are poorly known, particularly insects. To address this gap, we employed DNA barcoding to survey its insect diversity. Specimens obtained through diverse collecting methods at 1,858 sites across Pakistan from 2010–2019 were examined for sequence variation in the 658 bp barcode region of the cytochrome c oxidase 1 (COI) gene. Sequences from nearly 49,000 specimens were assigned to 6,590 Barcode Index Numbers (BINs), a proxy for species, and most (88%) also po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…In other research, similar variance in barcode recovery across several arthropod taxa has been documented. The sequence recovery rates ranging from 75% to 80% has been reported in various insect orders ( Park et al, 2011 ; Ashfaq et al, 2022 ). Moreover, similar trends of variation in sequence recovery rates in a broader scope has been reported across Canada, DNA barcoding was performed on 1,500,003 animal specimens across diverse taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…In other research, similar variance in barcode recovery across several arthropod taxa has been documented. The sequence recovery rates ranging from 75% to 80% has been reported in various insect orders ( Park et al, 2011 ; Ashfaq et al, 2022 ). Moreover, similar trends of variation in sequence recovery rates in a broader scope has been reported across Canada, DNA barcoding was performed on 1,500,003 animal specimens across diverse taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this potential capacity, the diversity of Hymenopteran insects in Balochistan has not been adequately explored. For instance, Ashfaq et al [ 75 ] conducted extensive research on identification of dominant insect orders including Coleoptera, Hemiptera, Hymenoptera and Lepidoptera that were captured by using Malaise traps in Pakistan. Studies have demonstrated that the HCNP, Hingol National Park (HNP) and other protected areas in Balochistan serve as biodiversity hotspots for various insects including bees, wasps, ants and sawflies [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to DNA contamination or damage during the extraction process. In an insect biodiversity surveillance effort in Pakistan, Ashfaq et al (2022) generated DNA barcodes for 60,273 specimens, leaving 17% of the specimens without DNA barcodes. Similarly, other studies by Geiger et al (2016) and Pentinsaari et al (2020) reported discrepancies in the sequences derived from various insect taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan encompasses four distinct biomes ( Afsar and Bano 2013 ), all potentially hosting a high diversity in life forms. However, still little is known about the true diversity of invertebrate fauna, insects in particular and some of these biomes remain poorly investigated ( Ashfaq et al 2022 ). This knowledge gap is particularly marked for the Ziarat Juniper ecosystem, where the few known species are those of phytosanitary interest, such as pests on Juniperus and cultivated plants ( Chaudhry 1979 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation